2017
DOI: 10.1111/1751-7915.12864
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of syngas‐converting communities from a multi‐orifice baffled bioreactor

Abstract: SummaryThe substitution of natural gas by renewable biomethane is an interesting option to reduce global carbon footprint. Syngas fermentation has potential in this context, as a diverse range of low‐biodegradable materials that can be used. In this study, anaerobic sludge acclimatized to syngas in a multi‐orifice baffled bioreactor (MOBB) was used to start enrichments with CO. The main goals were to identify the key players in CO conversion and evaluate potential interspecies metabolic interactions conferring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…Overall, the microbial composition found was in agreement with the catabolic routes identified for each enriched consortium in section 3.2 as most of the dominant genera identified could be associated with a specific microbial activity. Additionally, the results obtained here were highly consistent with other batch enrichment studies performed at similar conditions as the genera Acetobacterium and Methanospirillum were also found to be predominant by Arantes et al [16] at mesophilic conditions and the genus Thermincola by Alves et al [15] at thermophilic conditions. This indicates that the microbial selection process is somewhat independent of the inoculum used for the enrichment and shows high reproducibility, since microbial communities with very different initial microbial composition converged towards enriched cultures with high similarity as a result of the microbial selection driven by the operating conditions used.…”
Section: Microbial Composition Of Enriched Culturessupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, the microbial composition found was in agreement with the catabolic routes identified for each enriched consortium in section 3.2 as most of the dominant genera identified could be associated with a specific microbial activity. Additionally, the results obtained here were highly consistent with other batch enrichment studies performed at similar conditions as the genera Acetobacterium and Methanospirillum were also found to be predominant by Arantes et al [16] at mesophilic conditions and the genus Thermincola by Alves et al [15] at thermophilic conditions. This indicates that the microbial selection process is somewhat independent of the inoculum used for the enrichment and shows high reproducibility, since microbial communities with very different initial microbial composition converged towards enriched cultures with high similarity as a result of the microbial selection driven by the operating conditions used.…”
Section: Microbial Composition Of Enriched Culturessupporting
confidence: 92%
“…In the present study, the initial PCO was kept constant at 0.4 atm along the whole thermophilic microbial enrichment, which probably favored the prompt selection of hydrogenotrophic methanogenic species with higher tolerance to CO, allowing a complete conversion of syngas into CH4. Similarly, recent work on the enrichment of mesophilic mixed cultures using a multi-orifice baffled bioreactor (MOBB) sludge as initial inoculum reported a partial conversion of syngas into CH4 with acetate accumulation in the fermentation broth, which was attributed to a possible inhibition of aceticlastic methanogens due to the toxicity of CO [16].…”
Section: Enrichment Of Mesophilic and Thermophilic Mixed Culturesmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study, a complete CO consumption at nine days was shown, but not at four days [ 14 ]. Another study showed a complete CO consumption at 10 days [ 16 ]. Both studies exhibited similar mesophilic conditions and a headspace containing a volumetric CO concentration of 23.3% and 40% CO, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Improved methane productivity rates were reported by Strübing et al [34,35] when H2/CO2 methanation was performed under thermophilic conditions with mixed microbial consortia. Alternative reactor configurations reported in literature for syngas biomethanation are reverse membrane bioreactors [36,37] and multi-orifice baffled bioreactors [38].…”
Section: Introductionmentioning
confidence: 99%